THE USE OF PADLET FOR PEER ASSESSMENT: ITS EFFECT ON STUDENTS' ENGAGEMENT IN ENGLISH CLASSES - Iftia Rahmania; Muh Fajar (LPPM Universitas PGRI Jombang, 2026)
This study aimed to determine the effectiveness of Padlet in peer assessment on students’ engagement in the English classroom. The researcher used experimental research with a quasi-experimental design. Therefore, the researcher determines the experimental and control groups without random assignment. Both groups consisted of 29 students, with the total sample for this research was 58 students from the eleventh grade of State Senior High School in Jombang, East Java, Indonesia. Questionnaires were given to students as the instrument of the research. The data analysis using Analysis of Covariance (ANCOVA) was used to answer the research question. The result showed that the significance value of media or Padlet is 0.436, which is higher than the Alpha value, 0.05. It means the Null Hypothesis (H0) is accepted and the Alternative Hypothesis (Ha) is rejected. In other words, there is no significant difference in students’ engagement who are taught English using Padlet media and those who are not. Further, the initial conditions of engagement have a greater effect than the use of media (Padlet) on students’ engagement in the English classroom. The researcher suggests that future studies pay more attention to the initial conditions of student engagement and examine in greater depth factors other than media that may influence student engagement in English classroom.